Charged shells in a (2+1)-dimensional spacetime - Eiroa, Ernesto Fabian (2013)
We study circular shells in a (2+1)-dimensional background within the framework of Einstein-Born-Infeld theory. For shells around black holes we analyze the mechanical stability under perturbations preserving the symmetry. Shells around vacuum are also discussed. We find a large range in the values of the parameters compatible with stable configurations.